ANALISIS PERENCANAAN KEBUTUHAN MATERIAL PRODUK COINT BANK PADA USAHA RADHIN HANDYCRAFT KEDIRI - Rahadian Enggar Kusuma; Bambang Agus Sumantri (Cakrawala Management Business Journal, 2018)
Production planning is the most important thing in running an industry. This plan is related to determining the number of products that must be produced according to the production schedule, determining the material requirements for the fulfillment of production activities effectively. Radhin Handicrafts are classified as small and medium-sized businesses making souvenirs "coint bank", with the main material being cardboard and plywood tubes. The purpose of the study was to determine the amount of material from the Radhin Handycraft bank product and the total amount of material and component materials that must be provided to fulfill the order. Quantitative approaches, Material Requirement Planning methods determine and plan material requirements. Order data March 2018. The results is to fulfill the request in March 2018 as many as 600 pcs have not used special methods in planning the procurement of the required cardboard and plywood tubes. Fulfillment of their needs is based solely on traditional calculations according to the experience of previous production which is less efficient and inaccurate so that delays in delivery often occur due to the shortage of cardboard tube materials and sudden plywood. There needs to be an evaluation of planning methods for procuring cardboard and plywood tubes.